2013
DOI: 10.1016/j.canep.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Incidence patterns and trends of malignant gonadal and extragonadal germ cell tumors in Germany, 1998–2008

Abstract: Background Gonadal (GGCT) and extragonal germ cell tumors [GCT (EGCT)] are thought to originate from primordial germ cells. In contrast to well reported population-based data of GGCTs in males, analyses of GGCTs in females and EGCTs in both sexes remain limited. Methods In a pooling project of nine population-based cancer registries in Germany of the years 1998–2008, 16,883 GCTs and their topographical sites were identified using ICD-O morphology and topography for those aged 15 years and older. We estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 12 publications
4
49
0
1
Order By: Relevance
“…Sudden deaths due to extragonadal germ cell tumors are very rare. To begin with, extragonadal germ cell tumors (EGCTs) only represent 1.6–5% of all germ cell tumors . They occur along the median axis of the body with the anterior mediastinum being the most frequent extragonadal site (50–70%), followed by the retroperitoneum (30–40%) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sudden deaths due to extragonadal germ cell tumors are very rare. To begin with, extragonadal germ cell tumors (EGCTs) only represent 1.6–5% of all germ cell tumors . They occur along the median axis of the body with the anterior mediastinum being the most frequent extragonadal site (50–70%), followed by the retroperitoneum (30–40%) .…”
Section: Discussionmentioning
confidence: 99%
“…The majority (one‐third) of these tumors are soft tissue sarcomas—predominantly liposarcoma and leiomyosarcoma Extragonadal germ cell tumors are rare and only represent 1.6–5% of all germ cell tumors . The most common site of extragonadal manifestation is in the anterior mediastinum (50–70%) followed by the retroperitoneum (30–40%) . Sudden deaths due to undetected mediastinal germ cell tumors are rare .…”
mentioning
confidence: 99%
“…The incidence rates are 1.3/ 1 million for white males and 0.1/1 million for white females [13]. An epidemiologic study from Germany reported slightly lower incidence rates of mediastinal seminomas, non-seminomatous GCT in males, and non-dysgerminomas in females of 0.11, 0.2, and 0.03 per 1 million people, respectively [14]. In adults, PMGCTs occur predominantly in men; only approximately 9-14 % arise in women [13,[15][16][17].…”
Section: Demographicsmentioning
confidence: 94%
“…1 EGCTs often occur in the midline of the body, with the three most common sites in the anterior mediastinum, retroperitoneum, and pineal gland. 1,2 Epidemiologic studies suggest that although similar in morphologic appearance, the embryonic and genetic initiating events of EGCTs may be distinct from the gonadal germ cell tumours (GGCTs). [1][2][3][4] EGCTs, especially of the mediastinal origin, are often marked by inferior survival outcomes compared to GGCTs, as well as hematologic neoplasms (acute myeloid leukemia and malignant histiocytosis) and systemic mast cell disease that are unrelated to treatment effect.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Epidemiologic studies suggest that although similar in morphologic appearance, the embryonic and genetic initiating events of EGCTs may be distinct from the gonadal germ cell tumours (GGCTs). [1][2][3][4] EGCTs, especially of the mediastinal origin, are often marked by inferior survival outcomes compared to GGCTs, as well as hematologic neoplasms (acute myeloid leukemia and malignant histiocytosis) and systemic mast cell disease that are unrelated to treatment effect. 5,6 The usual treatment for EGCTs has been platinum-based chemotherapy regimen, such as bleomycin, etoposide and cisplatin (BEP), followed by surgical resection of residual tumours, if feasible.…”
Section: Introductionmentioning
confidence: 99%